O Processo de Escolha de Dirigentes Escolares e Seus Reflexos na Gestão Municipal de Novo Hamburgo/RS (2001-2009) - Escosteguy, Silvana Maria Ramos (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation has as its theme questions relating to school management, into a democratic approach. It realizes an investigation about the school principals of network municipal public school of Novo Hamburgo/RS, taking into account the different forms of choice to arrive to the exercise of the that function. Causing trouble in the different forms of provision to the post of school manager, assumed in this city, from the year 2001 until 2009, passing by the indication of school master by public power, by project of choice starting triple list and the proposal of direct election. Makes a historic trajectory of school administration since 1930, grounded in classic theoretical perspective in comparison with one education with the foreign countries, mainly the U.S, until today, when the school administration it becomes denominated school management, it becomes understood together with the economic impacts, political, social, cultural and technological of Brazil. Interprets the school management into a proposal that is not limited the bureaucratic functions technically, but in the beginning of its democratization and collective construction, by way of participation of citizenship, enabling the development of the transformer conscience of man in the world. The study broaches too the different administrative models: patrimonial, bureaucratic, managerialist and democratic, indentifying the forms of provision the function of the school principals of network municipal public of Novo Hamburgo/RS they intervened in course of the municipal management of education, have been analyzing the points and counterpoint of indication, of the triple list and the direct elections. The search it’s Qualitative and uses technical as the interview semistructured, questionnaire and document analysis, showing some of the democratic advances and regression in the history of Brazilian education and the movement by democratic school management in Rio Grande do Sul. The investigation it considers that municipal network of education cannot be democratized simply by democratization of its organizational structures and management, not just with the direct election of school principals, but yes through the its forms of intervention civic and sociocultural with the participation the whole school community.
Keywords: Gestão escolar democrática; Eleição direta; Indicação; Lista tríplice; Diretores escolares; Democratic school management; Direct election; Indication; Triple list; School principals; ACCNPQ::Ciências Humanas::Educação